Global trends in research related to emergence delirium, 2012–2021: A bibliometric analysis - Wang, Kenru; Cai, Jiehui; Du, Ruiming; Wu, Jiaxuan (Frontiers in Psychology, 2023)
Emergence delirium is a kind of mental disorder during the early awakening period after general anesthesia, which is manifested as the combination of perceptual disturbance and psychomotor agitation.It is an independent risk factor for postoperative delirium and even long-term postoperative cognitive decline, which often affects the postoperative outcome and deserves the attention of clinical anesthesiologists. There are many studies on emergence delirium, but the quantity and quality of these studies are unclear. Therefore, we conducted a bibliometric analysis of studies on emergence delirium between January 2012 and December 2021. Through the analysis of relevant literature, the research hotspots and trends of emergence delirium are understood, which can provide a reference for future research. We searched the Web of Science Core Collection (WoSCC) for original articles and reviews related to emergence delirium published between 2012 and 2021, and collected a variety of bibliographic elements, including annual publications, authors, countries/regions, institutions, journals, and keywords. Three different science-based tools (CiteSpace, VOSviewer and Bibliometrix) were used for this comprehensive analysis. From January 2012 to December 2021, a total of 912 emergence delirium (ED) related literature were published, including 766 original research articles and 146 review articles. The number of publications has increased every year except 2016. The United States published 203 articles, ranking first with China, followed by South Korea(95 articles). The United States is also the country with the most citations (4,508), and Yonsei Univ is the most productive institution. The most published journal was PEDIATRIC ANESTHESIA, with the highest h and g index. LEE JH is the most influential author in this field. "Children, emergence agitation, delirium, dexmedetomidine" are the hot topics in this field in recent years. The bibliometric analysis in this field will provide the future direction for the study of emergence delirium for clinicians.